Adolescent maturation of cortical excitation-inhibition ratio based on individualized biophysical network modeling - Saberi, Amin; Wischnewski, Kevin J.; Jung, Kyesam; Lotter, Leon D.; Schaare, H. Lina; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; et al. (Science advances, 2025)
The excitation-inhibition ratio is a key functional property of cortical microcircuits which changes throughout an individual’s lifespan. Adolescence is considered a critical period for maturation of excitation-inhibition ratio. This has primarily been observed in animal studies. However, there is limited human in vivo evidence for maturation of excitation-inhibition ratio at the individual level. Here, we developed an individualized in vivo marker of regional excitation-inhibition ratio in human adolescents, estimated using large-scale simulations of biophysical network models fitted to resting-state functional imaging data from both cross-sectional (n = 752) and longitudinal (n = 149) cohorts. In both datasets, we found a widespread decrease in excitation-inhibition ratio in association areas, paralleled by an increase or lack of change in sensorimotor areas. This developmental pattern was aligned with multiscale markers of sensorimotor-association differentiation. Although our main findings were robust across alternative modeling configurations, we observed local variations, highlighting the importance of methodological choices for future studies.
Online veröffentlicht: 4. Juni 2025
Gesehen am 15.09.2025